Nonfatal firearm injuries: Utilization and expenditures for children pre‐ and postinjury. (26th August 2021) - Pulcini, Christian D.; Goyal, Monika K.; Hall, Matt; Gruhler De Souza, Heidi; Chaudhary, Sofia; Alpern, Elizabeth R.; Fein, Joel A.; Fleegler, Eric W.
Abstract: Objective: Firearm injuries are one of the leading preventable causes of morbidity and mortality among children. Limited information exists about the impact of nonfatal firearm injuries on utilization and expenditures. Our objective was to compare health care encounters and expenditures 1 year before and 1 year following a nonfatal firearm injury. Methods: This was a retrospective cohort study of children 0 to 18 years with ICD‐9/ICD‐10 diagnosis codes for firearm injury (excluding nonpowder) in the emergency department or inpatient setting from 2010 to 2016 in the Medicaid MarketScan claims database. Outcomes included: (1) difference in health care encounters for 1 year before and 1 year after injury, (2) difference in health care expenditures, and (3) difference in complex chronic disease status. Descriptive statistics characterized patient demographics and health care utilization. Health expenditures were evaluated with Wilcoxon signed‐rank tests. Results: Among 1, 821 children, there were 22, 398 health care encounters before the injury and 28, 069 after. Concomitantly, there was an overall increase of 16.5 million in health expenditures (9, 084 per patient). There was a 50% increase in children qualifying for complex chronic condition status after firearm injury. Conclusions: Children who experience nonfatal firearm injury have increased number of health care encounters, chronic disease classification, and health care expenditures in the year following the injury. Prevention of firearm injuries in this vulnerable age group may result in considerable reductions in morbidity and health care costs.